2019
DOI: 10.3889/oamjms.2019.075
|View full text |Cite
|
Sign up to set email alerts
|

Construct and Psychometric Properties of a New Version Quality of Life Scale Based on Choice Theory

Abstract: BACKGROUND: Choice theory, as a psychopathological model, postulated five basics, genetically and universally, needs. Accordingly, the rate of everybody happiness and quality of life is depended on the number of his needs fulfilling. Although some scales have been constructed to assess basic needs, they have proposed unity of needs for all human. AIM: The present study was designed to construct a new scale, considering individualisation needs for each person; quality of life scale based on choice theory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Since choice theory emphasizes leisure activities and basic needs satisfaction, it has a remarkable positive impact on the patients, emotions, and sense of wellbeing. This finding is also in line with other research about the quality of life affecting by reality therapy (7).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Since choice theory emphasizes leisure activities and basic needs satisfaction, it has a remarkable positive impact on the patients, emotions, and sense of wellbeing. This finding is also in line with other research about the quality of life affecting by reality therapy (7).…”
Section: Discussionsupporting
confidence: 93%
“…Reality therapy improves internal control, which helps us to achieve our goals by managing our behavior, as opposed to external control, which focuses on controlling others. Besides, it illustrated the significant effect of our positive behavior and thinking on our feeling, which leads to improvement of mental health and reduction of anxiety and mood disorders (6,7). In previous studies, the effects of reality therapy on adults have been demonstrated.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…In this study, it was assumed that what led people to a successful or unsuccessful life was how they analysed different situations and their choices, as Glaser believed [ 1 ]. Based on this assumption, we selected two groups of people with different lifestyles who should indicate the difference between the two lifestyles.…”
Section: Discussionmentioning
confidence: 99%
“…"What we are today is the result of our past choices" [ 1 ] William Glaser, psychologist and the founder of Choice theory believed that the basic difference between humans is in their power of choice. The Choice theory leads us to the most fundamental human cognition.…”
Section: Introductionmentioning
confidence: 99%